2009
DOI: 10.3858/emm.2009.41.9.073
|View full text |Cite
|
Sign up to set email alerts
|

JNK inhibitor SP600125 promotes the formation of polymerized tubulin, leading to G2/M phase arrest, endoreduplication, and delayed apoptosis

Abstract: The JNK inhibitor SP600125 strongly inhibits cell proliferation in many human cancer cells by blocking cell-cycle progression and inducing apoptosis. Despite extensive study, the mechanism by which SP600125 inhibits mitosis-related effects in human leukemia cells remains unclear. We investigated the effects of SP600125 on the inhibition of cell proliferation and the cell cycle, and on microtubule dynamics in vivo and in vitro. Treatment of synchronized leukemia cells with varying concentrations of SP600125 res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 41 publications
3
26
0
Order By: Relevance
“…TNF-α treatment increased the phosphorylation of JNK and its downstream target, c-Jun, within five min ( Figure 5A). Although a previous report has shown that SP600125, a JNK inhibitor, promotes apoptosis in human leukemia cells (Moon et al, 2009), it did not exert cytotoxic effects on C2C12 cells at 10 μM concentration ( Figure 5B). RT-PCR and immunoblot analyses revealed that Msx2 induction by TNF-α was not affected by SP600125 treatment.…”
Section: Resultsmentioning
confidence: 55%
“…TNF-α treatment increased the phosphorylation of JNK and its downstream target, c-Jun, within five min ( Figure 5A). Although a previous report has shown that SP600125, a JNK inhibitor, promotes apoptosis in human leukemia cells (Moon et al, 2009), it did not exert cytotoxic effects on C2C12 cells at 10 μM concentration ( Figure 5B). RT-PCR and immunoblot analyses revealed that Msx2 induction by TNF-α was not affected by SP600125 treatment.…”
Section: Resultsmentioning
confidence: 55%
“…The monomeric fraction was prepared by extracting cells in monomeric extraction buffer (20 mM PIPES, 0.14 M NaCl, 1 mM MgCl 2 , 1 mM EGTA, 0.5% NP-40, and 0.5 mM PMSF, pH 6.8) as previously described [34] with some modifications. After centrifugation at 13,000 Â g for 10 min at room temperature, the NP-40-soluble fraction containing monomeric tubulin was collected.…”
Section: Extraction Of Monomeric and Polymeric Tubulinmentioning
confidence: 99%
“…Our data suggest that JNK may be required for the separation or localization of the centrosome in the cell poles, therefore controlling the separation of chromatids at the outset of anaphase, and possibly helping to prevent polyploidy. It has, indeed, been shown that inhibition of JNK results in polyploidy and apoptosis of cultured cell lines [37], [40]. Thus, JNK may be important to maintain genomic stability and prevent programmed cell death in progenitor cells during retinal development.…”
Section: Discussionmentioning
confidence: 99%
“…The data suggest that the JNK signaling pathway may be involved in controlling the M-phase of the cell cycle [35][40]. Most studies, however, were done in either tumor cell lines [20]–[22], [36][41] or dissociated cells [23], [24], [35], [42], and little is known of the role of this enzyme in cell proliferation in the central nervous system [43][45].…”
Section: Introductionmentioning
confidence: 99%